Association of depressiveness with chronic facial pain: A longitudinal study. (May 2013) - Sipilä, Kirsi; Mäki, Pirjo; Laajala, Anne; Taanila, Anja; Joukamaa, Matti; Veijola, Juha
Abstract Objective. Depression and pain are often co-morbid. Temporomandibular disorders (TMD) include facial pain as one main symptom. Reports are lacking on the association between chronic facial pain and earlier depressiveness. The aim of the study was to investigate whether depressiveness increases the risk for chronic facial pain in a longitudinal population-based study. Materials and methods. Subjects included in the Northern Finland Birth Cohort 1966 (n = 5696) answered a questionnaire on facial pain and depressiveness using the Symptom Checklist-25 depression sub-scale at the age of 31 years. In addition, reported depression diagnosed by a doctor was enquired about. Three years later a sub-sample of the cohort, including 63 cases with chronic facial pain and 85 pain-free controls, was formed based on the question concerning facial pain. Results. Of the chronic facial pain cases 17.5% and of the pain-free controls 7.1% were depressive 3 years earlier at baseline (p = 0.050, χ2 test, crude OR = 2.8, 95% CI = 1.0–8.0). Of the chronic facial pain cases 6.3% and of the pain-free controls 1.2% reported having had diagnosed depression (p = 0.085, crude OR = 5.7, 95% CI = 0.6–52.2). After adjusting the gender, the association between depressiveness reported at the baseline and chronic facial pain was significant (OR = 4.2, 95% CI = 1.1–16.2). When widespread pain was included in the analysis, the association was not significant. Conclusions. Depressiveness increases the risk for chronic facial pain in a 3-year follow-up. This association seems to be mediated through widespread pain.